Biocompatibility and Toxicity of Poly(vinyl alcohol)/N,O-Carboxymethyl Chitosan Scaffold - Tunku Kamarul; G. Krishnamurithy; Noman D. Salih; Nurul Syuhada Ibrahim; Hanumantha Rao Balaji Raghavendran; Abdul Razzaq Suhaeb; D. S. K. Choon (The Scientific World Journal)
The in vivo biocompatibility and toxicity of PVA/NOCC scaffold were tested by comparing them with those of a biocompatible inert material HAM in a rat model. On Day 5, changes in the blood parameters of the PVA/NOCC-implanted rats were significantly higher than those of the control. The levels of potassium, creatinine, total protein, A/G, hemoglobulin, erythrocytes, WBC, and platelets were not significantly altered in the HAM-implanted rats, when compared with those in the control. On Day 10, an increase in potassium, urea, and GGT levels and a decrease in ALP, platelet, and eosinophil levels were noted in the PVA/NOCC-implanted rats, when compared with control. These changes were almost similar to those noted in the HAM-implanted rats, except for the unaltered potassium and increased neutrophil levels. On Day 15, the total protein, A/G, lymphocyte, monocyte, and eosinophil levels remained unaltered in the PVA/NOCC-implanted rats, whereas urea, A/G, WBC, lymphocyte, and monocyte levels remained unchanged in the HAM-implanted rats. Histology and immunohistochemistry analyses revealed inflammatory infiltration in the PVA/NOCC-implanted rats, but not in the HAM-implanted rats. Although a low toxic tissue response was observed in the PVA/NOCC-implanted rats, further studies are necessary to justify the use of this material in tissue engineering applications.